The Structure of Advertising Texts - Smetonienė, Irena (Kalbotyra, 2000)
One of the aspects of advertising studies is the linguistic analysis of text. The composition of an audio advertisement text is similar to the composition of public language: introduction, the main text and the end (address or slogan). The texts do not necessarily have to consist of all the parts nor do they have to be presented in the said order. All depends on the advertised product and on the plan of presentation. Advertisement text writers pay special attention to the slogan; they make the greatest demands on it.